Case studies on the safety management at construction site - Tan, Chin Keng; Abdul Razak, Nadeera (Universiti Malaysia Terengganu, 2014)
Cases of construction site accidents always happen. In line with the efforts to reduce accidents at construction sites in Malaysia, the objectives of this research are to determine the current safety practices at construction sites, to identify the safety practices related problems, and to identify the strategies to reduce the safety practices related problems. Two case studies were conducted for data collection. Data were collected through semi-structured interviews with the safety officer of the respective project. It is concluded from the research findings that generally the construction site has good and structured as far as safety practices are concerned. Among the practices are safety policy, education and training, site safety inspection, safety auditing, safety meeting, site safety organization, personal protective equipments, emergency support and safety measuring devices, fall protective systems, and safety promotions. Nevertheless, several problems are encountered in the safety practices; the problems are ignorance of workers on work procedures, lack of financial allocation for safety management, lack of awareness among workers, and language barrier between supervisors and workers. Several strategies have been suggested to overcome the problems, the strategies are to provide effective safety training, allocation of budget for safety management, full commitment from the top management, and to provide safety booklets in various languages as the strategies to reduce problems in safety practices. The suggestion cover three aspects for the implementation of safety practices, i.e. awareness of workers, commitment of top management and the allocation of resources. The findings of this research would reduce the gap of understanding on the aspect of safety practices at construction site in Malaysia and can be used as construction practitioners as a source of reference in their site safety management.